Differences in perceived benefits of internships for subgroups of students with disabilities. - Burgstahler S; Bellman S (Journal of Vocational Rehabilitation, 2009)
The authors of this article share the results of a study that compares specific benefits of internships completed by students with disabilities, as perceived by males and females, high school and college students, Caucasian and non-Caucasian students, and students with invisible disabilities and those with visible disabilities. Students in the study completed six- to twelve-week internships in fields that included computing, biology, engineering, research, administration, and health science. In a post-internship survey, participants reported gains in their motivation to work toward a career, knowledge of career options, job skills, ability to work with supervisors and co-workers, and knowledge of accommodation strategies. Analysis of participant responses revealed differences in perceived gains between respondents. The authors share lessons learned that may help career development, cooperative education, counseling, advising, and human resource professionals more effectively support high school and college students with disabilities who engage in internships.